PENGARUH DEBT TO EQUITY RATIO (DER) DAN DEBT TO ASSET RATIO (DAR) TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BEI (STUDI KASUS PADA PT BUKIT ASAM TBK) - Pratiwi, Shela Oktarina (Jurnal Enterpreneur dan Bisnis (JEBI), 2023)
This study aims to determine the effect of Debt To Equity Ratio (DER) and Debt To Asset Ratio (DAR) on the Value of Companies Listed on the IDX (Case Study at PT Bukit Asam Tbk). The information used in this survey is quantitative information. The sample in this survey hour is information on the quarterly fiscal overview of PT Bukit Asam Tbk for the 2014-2021 period totaling 32 data. From the results of the F test test which shows that Fhitung Ftabel (12.601 3.30) with a sig value of 0.19 0.05, then simultaneously DER and DAR have a significant effect on the Price Book Value. According to the results of the t test in this study, it can be concluded that the independent variable DER with a calculated value of ttabel (-2.280 1.669) and a sig value of 0.030 0.05, it can be concluded that DER has a negative and significant effect on the Price Book Value. According to the results of the t test of the DAR variable with a calculated value of ttable (2.195 1.669) and a sig value of 0.036 0.05, it can be implied that the DAR variable has a significant effect on the Price Book Value